Flow Diversion of Posterior Circulation Aneurysms: Systematic Review of Disaggregated Individual Patient Data - Alwakeal, A.; Shlobin, N.A.; Golnari, P.; Metcalf-Doetsch, W.; Nazari, P.; Ansari, S.A.; Hurley, M.C.; Cantrell, D.R.; Shaibani, A.; Jahromi, B.S.; Potts, M.B. (American Journal of Neuroradiology, 2021)
BACKGROUND: Experience with endoluminal flow diversion for the treatment of posterior circulation aneurysms is limited.PURPOSE: We sought to investigate factors associated with the safety and efficacy of this treatment by collecting disaggregated patient-level data from the literature.DATA SOURCES: PubMed, EMBASE, and Ovid were searched up through 2019 for articles reporting flow diversion of posterior circulation aneurysms.STUDY SELECTION: Eighty-four studies reported disaggregated data for 301 separate posterior circulation aneurysms.DATA ANALYSIS: Patient, aneurysm, and treatment factors were collected for each patient. Outcomes included the occurrence of major complications, angiographic occlusion, and functional outcomes based on the mRS.DATA SYNTHESIS: Significant differences in aneurysm and treatment characteristics were seen among different locations. Major complications occurred in 22%, angiographic occlusion was reported in 65% (11.3 months of mean follow-up), and good functional outcomes (mRS 0–2) were achieved in 67% (13.3 months of mean follow-up). Multivariate analysis identified age, number of flow diverters used, size, and prior treatment to be associated with outcome measures. Meta-analysis combining the current study with prior large nondisaggregated series of posterior circulation aneurysms treated with flow diversion found a pooled incidence of 20% (n = 712 patients) major complications and 75% (n = 581 patients) angiographic occlusions.LIMITATIONS: This study design is susceptible to publication bias. Use of antiplatelet therapy was not uniformly reported.CONCLUSIONS: Endoluminal flow diversion is an important tool in the treatment of posterior circulation aneurysms. Patient age, aneurysm size, prior treatment, and the number of flow diverters used are important factors associated with complications and outcomes.aORadjusted ORFDflow diverterPCAposterior cerebral arteryVBJvertebrobasilar junction